Loss Function Influence on Uncertainty Estimation for White Matter Lesions 3D Segmentation in a Shifted Domain Setting - Kaczmarska, Marta; Majek, Karol (Wydawnictwo Politechniki Łódzkiej, 2023)
The aim of this study is to address the problem of distributional shift for white matter Multiple Sclerosis lesion segmentation models. The impact of loss function on models performance and uncertainty estimation is evaluated. The evaluation is performed on two in-domain and one out-ofdomain dataset consisting of 3D FLAIR Magnetic Resonance images. Our experiments show that application of segmentation losses (eg. Dice) translate into reduced models robustness and poorer uncertainty estimation compared with classification losses (eg. CE). The source code is publicly available.
Keywords: white matter multiple sclerosis lesions; multiple sclerosis; 3D segmentation; magnetic resonance imaging; zmiany w istocie białej w stwardnieniu rozsianym; stwardnienie rozsiane; segmentacja 3D; rezonans magnetyczny